MOTION OR REST: WHAT IS MORE PREFERABLE FOR PATIENTS WITH JUVENILE IDIOPATHIC ARTHRITIS? - T. A. Shelepina (Современная ревматология)
The paper reviews the literature dealing with juvenile idiopathic arthritis (JIA) prognosis, patient physical activity, its role in the development of functional problems that cause limited vital activity and reduced quality of life, as well as the efficiency of physical exercises (exercise therapy (ET)) in the treatment of this disease. It stresses the relationship between physical developmental delay in patients with JIA and the occurrence of psychological and social problems. There are data of publications about the need for physical loads for patients with various rheumatic diseases, as well as for adults. Special attention is paid to the good endurance of ET that is identified by a number of authors as an additional treatment for JIA patients, which improves their functional status, but fails to affect the course and outcome of the disease. The author analyzes survey papers on the multidisciplinary rehabilitation of children, adolescents in particular, and the importance of science-based propaganda of active lifestyle. By having analyzed the literature, the author concludes that it is expedient to include ET into standard treatment for patients with JIA.